Comparing frugivorous butterfly species under different agricultural landscapes - Zakaria, Najihah (2018)
The conversion of native forests to monoculture plantation has taken a spotlight in biodiversity-rich countries in the tropics. This has lead to biodiversity loss of insects that play important role in ecosystem functioning. The present study investigates the effect of different vegetation structure and microclimatic condition between monoculture and polyculture plantations on frugivorous butterfly diversity and abundance. The study was conducted in Kampung Sungai Lalah, Pedas, Negeri Sembilan. For the study, monoculture farming systems were conducted in oil palm and rubber plantations, while polyculture farming systems was conducted in orchard. Passive sampling was used to capture fruit feeding butterflies at all study areas. A total of 15 sampling point were set up in each agricultural landscape giving a total of 45 sampling points. Each sampling points were randomly selected with > 100 m distance. Butterflies were sampled in 28 day period between January to February 2018 where five sampling points were completed for every three days. The result showed a total of 363 frugivorous butterflies belonging to 7 species were recorded under the subfamily of Satyrinae and Limenitidinae. The highest occurrence was recorded in orchard, followed by oil palm and rubber plantation. It is proven that fruit feeding butterfly abundance and species richness were greater in polyculture (orchard) than monoculture plantations (oil palm and rubber plantations).The findings of this study suggest that spatial heterogeneity greatly influences patterns in butterfly species richness and abundance. Thus, polyculture farming should be explicitly considered in conservation and management actions.